Anti-biofilm properties of the antimicrobial peptide temporin 1Tb and its ability, in combination with EDTA, to eradicate Staphylococcus epidermidis biofilms on silicone catheters. Issue 7 (8th August 2016) - Maisetta, Giuseppantonio; Grassi, Lucia; Di Luca, Mariagrazia; Bombardelli, Silvia; Medici, Chiara; Brancatisano, Franca Lisa; Esin, Semih; Batoni, Giovanna
Abstract: In search of new antimicrobials with anti-biofilm potential, in the present study activity of the frog-skin derived antimicrobial peptide temporin 1Tb (TB) against Staphylococcus epidermidis biofilms was investigated. A striking ability of TB to kill both forming and mature S. epidermidis biofilms was observed, especially when the peptide was combined with cysteine or EDTA, respectively. Kinetics studies demonstrated that the combination TB/EDTA was active against mature biofilms already after 2–4-h exposure. A double 4-h exposure of biofilms to TB/EDTA further increased the therapeutic potential of the same combination. Of note, TB/EDTA was able to eradicate S. epidermidis biofilms formed in vitro on silicone catheters. At eradicating concentrations, TB/EDTA did not cause hemolysis of human erythrocytes. The results shed light on the anti-biofilm properties of TB and suggest a possible application of the peptide in the lock therapy of catheters infected with S. epidermidis .